2017
DOI: 10.4236/ojogas.2017.22005
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Degradation of Oilfield Wastewater Treatment by Three-Dimensional Electrode

Abstract: The COD value is the main control index of sewage standard. The method of three-dimensional electrocatalytic oxidation is studied for deep treatment of oilfield sewage. The oxidation mechanism and the structure of the three-dimensional electrode reactor are analyzed and optimized. A series of single factor experimental results show that each control parameter has different influences on COD removal rate in the process of oxidative degradation. Based on the experimental study of electrode materials, electrode f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The proposed models (Equations and ) validation is checked by comparing the coefficient of determination with Gelatin product used in Schneider 47 study, the residual organic matter product used in Arras 48 study and Sludge product used in Liu et al 49 study as given in Figure 7. The proposed models (Equations and ) have the highest coefficient of determination.…”
Section: Modeling Of Resultsmentioning
confidence: 99%
“…The proposed models (Equations and ) validation is checked by comparing the coefficient of determination with Gelatin product used in Schneider 47 study, the residual organic matter product used in Arras 48 study and Sludge product used in Liu et al 49 study as given in Figure 7. The proposed models (Equations and ) have the highest coefficient of determination.…”
Section: Modeling Of Resultsmentioning
confidence: 99%
“…Many researches have focused on designing new ways and adding various chemical compositions to improve the electro-catalytic activity and chemical stability. Some types of metal oxide electrodes, such as SnO 2 , PbO 2 , Sb 2 O 3 , RuO 2 and composite oxides, have been widely studied, [7][8][9][10][11] and the higher reaction activity is expected all the time.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that graphite electrodes can easily react with electrochemically produced oxygen forming CO and CO 2 , resulting in its corrosion (Liu et al 2017). ) (Gamby et al 2001).…”
Section: Characterization Of Simulated Greywatermentioning
confidence: 99%
“…However, the higher conductivity of the GG may favour the occurrence of electrochemical reactions onto its surface when it is polarized, (Brown et al 2004a, Brown et al 2004b. As graphite electrodes have been reported to present a low mechanical strength, the electrochemically produced ROS species can react with the graphite resulting in its corrosion (Liu et al 2017). Therefore, the lower values obtained for the kinetic constant in the 3D system (k 3 ) using GG for the treatment of SGW also suggest that the produced oxidant species may be reacting with the GG rather than oxidising the pollutants.…”
Section: Kinetic Constants and Synergy Valuesmentioning
confidence: 99%
See 1 more Smart Citation